2016
DOI: 10.1177/1948550616630032
|View full text |Cite
|
Sign up to set email alerts
|

Personality Trait Development During the Transition to Parenthood

Abstract: Social investment theory (SIT) proposes that the transition to parenthood triggers positive personality trait change in early adulthood. Using data from a representative sample of first-time parents compared to nonparents, the results of rigorous tests do not support the propositions of SIT. Specifically, we found no evidence for the proposition that parents show more pronounced mean-level increases in emotional stability, agreeableness, and conscientiousness compared to nonparents. We did find that agreeablen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
147
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 165 publications
(166 citation statements)
references
References 44 publications
17
147
2
Order By: Relevance
“…This latter study also found that, in the years after childbirth, parents decreased in emotional stability, offsetting the positive anticipation effect on this trait. In contrast, two other studies with 2-wave designs did not find evidence for change in any of the Big Five personality traits during the transition to parenthood (Neyer & Asendorpf, 2001;van Scheppingen et al, 2016). For self-esteem, a recent 5-wave longitudinal study of newlyweds found sudden declines in the year after childbirth and gradual decreases in the following 3 years after .…”
Section: Previous Research On Parenthood and Personality Changementioning
confidence: 79%
See 4 more Smart Citations
“…This latter study also found that, in the years after childbirth, parents decreased in emotional stability, offsetting the positive anticipation effect on this trait. In contrast, two other studies with 2-wave designs did not find evidence for change in any of the Big Five personality traits during the transition to parenthood (Neyer & Asendorpf, 2001;van Scheppingen et al, 2016). For self-esteem, a recent 5-wave longitudinal study of newlyweds found sudden declines in the year after childbirth and gradual decreases in the following 3 years after .…”
Section: Previous Research On Parenthood and Personality Changementioning
confidence: 79%
“…Using 2-wave longitudinal data with a 4-year time interval, van Scheppingen et al (2016) have found a small anticipatory increase in fathers' openness in the years before childbirth, as compared to a control group of nonparents. Second, Denissen et al (2018) have used data from up to 8 measurements of Big Five personality traits across 9 years and found that parents increased in emotional stability in the years before childbirth.…”
Section: Previous Research On Parenthood and Personality Changementioning
confidence: 95%
See 3 more Smart Citations